The Effectiveness of Herbal Interventions in Reducing Dysmenorrhea: A Scoping Review - Saputri, Meilina Intan Dewi; Supriyadi, Supriyadi; Santosa, Bedjo (Faculty of Public Health, Universitas Diponegoro, Semarang, Indonesia, 2025)
Introduction: Dysmenorrhea is a prevalent reproductive condition among adolescents and women of reproductive age. The prevalence of primary dysmenorrhea in Indonesia is 91.27 %. Analgesic drugs are frequently used to relieve pain; however, their potential side effects are common. Consequently, interest in herbal treatments has increased, as they are perceived to be safer and more suitable for the sustainable long-term management of dysmenorrhea. This scoping review aimed to identify herbal remedies that can reduce dysmenorrhea symptoms and the administration method.Methods : A scoping review was conducted following the PRISMA guidelines, searching Garuda and PubMed for articles published between 2015 and 2024 using the keywords “Dysmenorrhea” AND “Herbal Treatment.” Experimental or quasi-experimental studies on herbal interventions for primary dysmenorrhea were included, and data were descriptively analyzed to assess the types of herbs, administration methods, and their effects on pain. Fourteen studies met the inclusion criteria.Results: Herbal agents, such as ginger, mint, cinnamon, chamomile, licorice, turmeric, tamarind, evodia fruit, and traditional Thai and Chinese formulations, were found to be effective in alleviating dysmenorrhea, likely due to their anti-inflammatory, analgesic, and antispasmodic mechanisms. The administration was mostly through oral intake in the form of drinks, syrup, capsules, and infusion, and also through aromatherapy.Conclusion: Herbs, including ginger, chamomile, cinnamon, licorice, and multi-herbal formulations, can serve as safe complementary therapies, particularly for individuals intolerant to conventional medications such as NSAIDs. Nonetheless, further research with stronger study designs and standardized dosages is required to support broader, affordable, and practical applications in the general population of the general population